A BALLERINA'S SELF-DEFENSE MECHANISM : AN ANALYSIS OF NINA SAYERS CHARACTER IN BLACK SWAN MOVIE SCRIPT BY MARKHEYMAN,ET AL. - Marlina, Titi; Tuaderu, Yohanes (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
This study examines Darren Aronofsky’s Black Swan as the object of analysis. It portrays the psychological struggles of Nina Sayers, a ballerina who faces intense pressure to achieve perfection. The film illustrates how Nina confronts both internal conflict and external demands from her professional environment and family, reflecting the challenges of mental health in real-life experienced by individuals in competitive settings. The research applies a psychoanalytic approach to analyse the film script, employing Anna Freud’s theory on defence mechanisms, including repression, denial, reaction formation, and identification with the aggressor. The study identifies how Nina’s reliance on these mechanisms as an emotional survival strategy but gradually contributes to her psychological instability. The findings indicate that the persistent use of defence mechanisms leads Nina to rebel against her surroundings by acting in ways opposite to her true feelings, which results in her psychological breakdown. The study concludes that while defence mechanisms may temporarily protect individuals from stress, their excessive use can distort personality development. This research emphasizes the importance of recognizing the psychological impacts of pressure in high-performance environments and highlights the need for greater mental health awareness, particularly in the performing arts.